On the paradox of ion channel blockade and its benefits in the treatment of Alzheimer disease - Schmitt, Horst Peter (Medical hypotheses, 2005)
The surprisingly beneficial effects in Alzheimer disease (AD) of ion channel blockers (ICB) like memantine that act on NMDA- and other aminergic transmitter receptors are yet poorly understood. NMDA receptor levels and binding were shown to be significantly decreased in AD, in which highly NMDA receptor and Ca(2+) dependent synaptic plasticity and re-modelling are severely compromised. Thus, how could one expect to improve AD by further suppressing NMDA channels with antagonists. Nevertheless, clinical trials with NMDA blockers revealed in moderate to advanced AD surprisingly positive effects. The present paper tries to provides a hypothetical explanation of that paradoxical success of ICBs. Based on evidence from current data, emphasis is put on a profound impairment in the AD brain of the inhibition-excitation balance in the neuronal circuitry to the advantage of excitation. This imbalance is conceived to result from a degeneration of four modulatory aminiergic transmitter systems (serotonin, noradrenalin, acetylcholine, histamine) and related peptidergic systems, the decline of which causes a profound loss of inhibitory impact in the forebrain neuronal circuitry leading to disinhibition of principal neurones ("aminergic disinhibition"). Subsequent Ca(2+) excito-toxicity and its sequelae are suggested to be the basic promotors of the neuro-degeneration and the related mental decline in AD. Re-adjustment of the inhibition-excitation imbalance by decreasing excitation is conceived to be the mechanism that renders ion channel blockade therapeutically successful. Putatively, attempts to increase inhibition, e.g., by application of GABA mimetics that stimulate the production GABA from preserved but "lazy" GABA neurones lacking aminergic facilitation, might be an even better way to achieve the re-balance.